Checklists of Fish Species Infected with Species of the Genus Clinostomum Leidy, 1856 (Platyhelminthes: Trematoda), the Causative Agents of the Yellow Grub Disease, in Iraq - Mhaisen (Iraqi Journal of Aquaculture, 2025)
A survey of 60 references concerning the occurrence of species of the trematode genus Clinostomum Leidy, 1856 parasitizing freshwater fishes and one marine fish of Iraq indicated that there are three identified species of this genus: C. complanatum, C. dasi and C. tilapiae as well as some unidentified species of this genus infecting 29 fish species. The infections were distributed mainly in fishes from different inland water bodies as well as in two fishponds in Baghdad and Babylon provinces. Among the infected fishes, Carasobarbus luteus, Coptodon zillii, Cyprinus carpio and Heteropneustes fossilis were infected with the highest number of Clinostomum species (two parasite species each), while the remaining fish species were each infected with only C. complanatum. Among such trematodes, C. complanatum was infecting all 29 fish species, followed by C. dasi and C. tilapiae, which infected two and one fish species, respectively.